A Modern Vision of Methodological Approaches in Regulation of Labor Relations - OSTAPENKO, Oleksii I.; OSTAPENKO, Leonid O.; KHYTRA, Oleksandra L.; TSVOK, Maryana; VASYLIV, Solomia (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
Legal relations in labor activity are constantly undergoing reform in Ukrainian legislation. The reason for the reform can be considered the imperfection and instability of labor relations. These factors indicate the need to study legal relations in labor activities and understand the methodological approaches and the justification for reforming legislation. Based on the use of both general theoretical and branch scientific provisions, in particular labor law, it has been proposed in this research to develop main fundamental approaches to the methodology of legal regulation of labor relations in the context of modern development of Ukraine. The study revealed that the methods, methods and techniques used in the scientific knowledge of labor phenomena are interconnected and contribute to the formation of labor relations in the world of work. Conclusions are made regarding the nature and effectiveness of methodological approaches, their relationship with the principles of theoretical and practical activity of subjects of labor relations.